The Factors of Information Exposure, Cost and Community Perception on Utilization of Traditional Health Services - Teuku Reza Fadly; Sutopo Patria Jati; Ayun Sriatmi (Green Publisher Indonesia, 2025)
Traditional health care remains the community's choice in the midst of the modern health care system. However, their utilization is not optimal due to various factors. This study aims to analyze the influence of these three factors on the utilization of traditional health services in Pekalongan City. This study used a cross-sectional design with a quantitative approach. A sample of 393 respondents was selected using proportional random sampling technique. Data were collected through a structured questionnaire and analyzed using the Chi-square test and multiple logistic regression. The results of the analysis showed that cost and perception variables were related to utilization, but the information exposure factor was not statistically proven to be related. Cost was the largest influencing factor, with respondents who rated the cost of services as affordable being 3.5 times more likely to utilize traditional services. Cost and perception contribute to the utilization of traditional health services. Policies that focus on improving community perceptions and affordability are needed.